TanP: A Multifunctional Anionic Peptide From Tityus stigmurus Scorpion Venom - Melo, Menilla Maria Alves de; Oliveira, Verônica da Silva; Queiroz Neto, Moacir Fernandes de; Paiva, Weslley de Souza; Torres-Rêgo, Manoela; Silva, Sérgio Ruschi Bergamachi; Pontes, Daniel de Lima; Rocha, Hugo Alexandre Oliveira; Souza, Miguel Ângelo Fonseca de; Silva-Júnior, Arnóbio Antônio da; Fernandes-Pedrosa, Matheus de Freitas (Frontiers in Molecular Biosciences, 2022)
Anionic peptides of scorpions are molecules rich in aspartic and/or glutamic acid residues and correspond to a class of peptides without disulfide bonds still little explored. TanP is a linear anionic peptide (50 amino acid residues and net charge -20) present in the venom gland of the scorpion Tityus stigmurus with chelating properties for Cu2+ ion and immunomodulatory properties. The therapeutic application of chelating molecules is related to cases of acute or chronic intoxication by metals, neurodegenerative diseases, hematological diseases, healing of skin wounds, cardiovascular diseases and cancer. In this approach, the chelating activity of TanP was evaluated in relation to new metals of biological importance ions (Fe2+ and Zn2+), as well as its antioxidant, hemostatic, immunomodulatory and healing potential, aiming to expand the biological and biotechnological potential of this peptide. TanP (25 µM) was able to form stable complexes with Fe2+ in a ratio of 1:5 (TanP: Fe2+). Theoretical results suggest that TanP can work as a sensor to identify and quantify Fe2+ ions. The fluorescence intensity of TanP (1.12 µM) decreased significantly after the addition of Fe2+, obtaining that the highest ratio 1: 7.4 (TanP: Fe2+) led to the lowest fluorescence intensity. For Zn2+ no relevant spectral change was noted. TanP (50 µM) showed a maximum of 3% of hemolytic activity, demonstrating be biocompatible, as well as exhibited a DPPH radical scavenging activity above 70% at all concentrations tested (1 to 25 μM), 89.7% iron chelating activity at 25 μM and 96% hydroxyl radical scavenging activity at 73.6 μM. In addition, the TanP (12.5 µM and 25 µM) revealed an anticoagulant effect, prolonging the clotting time in prothrombin time (TP) and activated partial thromboplastin time (TTPa) assays, with no fibrinogenolytic activity. The TanP (12.5 and 25 µM) induced release of TNF-α by murine macrophages cells, in the absence of lipopolysaccharides, with a concentration-dependent increase, and also stimulated the migration of 3T3 cells in the in vitro healing assay. Thus, TanP revealed a multifunctional potential, being useful as a prototype for the development of new therapeutic and biotechnological agents.